All-polymer nano-structure dielectric thin film with self-assembled nano-scale multiple interfaces and preparation method of all-polymer nano-structure dielectric thin film

By using a self-assembled nanoscale multi-interface structure of thermoplastic resin and bismaleimide resin in polymer dielectric materials, the problem of insufficient dielectric energy storage performance at high temperature is solved, and high-efficiency energy storage in high temperature environments is achieved Performance, suitable for electronic equipment in high temperature environments.

CN119264660AActive Publication Date: 2025-01-07SHENZHEN UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411501775.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-01-07
Estimated Expiration
2044-10-25

AI Technical Summary

Technical Problem

The existing polymer dielectric materials have insufficient dielectric energy storage performance at high temperatures, resulting in increased conductivity loss, reduced breakdown field strength, and significantly reduced charge and discharge efficiency and energy storage density, making it difficult to meet the needs of electronic equipment in high temperature environments.

Method used

Self-assembled nanoscale multi-interface structure dielectric films using thermoplastic resin and bismaleimide resin. Through the specific ratio of thermoplastic polymer and bismaleimide resin and the coordination of catalyst, a complete range with excellent dielectric properties is formed. Polymer nanostructured dielectric films are prepared by heat treatment and film removal technology.

Benefits of technology

Under conditions of 150℃ and above 600MV/m, the leakage current is significantly reduced, the dielectric energy storage performance is improved, and the high breakdown field strength is provided, excellent charging and discharging efficiency and discharge energy density are suitable for energy storage capacitors in high-temperature environments and Microelectronics devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119264660A_ABST
    Figure CN119264660A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of dielectric materials and energy storage materials, in particular to an all-polymer nano-structure dielectric thin film with self-assembly nano-scale multiple interfaces and a preparation method of the all-polymer nano-structure dielectric thin film. In the components of the film material, the following requirements are met: the mass ratio of the thermoplastic resin to the bismaleimide resin is 95: 5-65: 35; the addition amount of the catalyst is 0.05 wt%-2wt% of the weight of the bismaleimide resin. The film provided by the invention can meet the application requirements under the conditions of 150 DEG C and more than 600MV / m. The thermoplastic resin component in the thin film endows the thin film with good flexibility, and the thin film is suitable for winding and laminating processes of thin film capacitors; and a bismaleimide (BMI) nanoscale multi-interface structure effectively obstructs injection and excitation of charges and remarkably reduces leakage current under high temperature and strong electric fields, so that the dielectric energy storage performance of the material under the conditions of high temperature and strong electric fields is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of dielectric materials and energy storage materials, and in particular to a full-polymer nanostructured dielectric film with self-assembled nanoscale multi-interfaces and a preparation method thereof. Background Art

[0002] Polymer dielectric film capacitors play an irreplaceable role in the electronic and electrical fields due to their advantages such as fast charging and discharging, high power density, excellent voltage resistance, self-healing ability and resistance to chemical corrosion. As electronic equipment develops towards miniaturization and lightweight, and the demand for application in extreme environments is increasing, higher requirements are placed on the energy storage performance and reliability of polymer dielectrics at high temperatures. Under the action of an external electric field, when the external temperature approaches the glass transition temperature of the polymer, the leakage current inside the dielectric will increase exponentially and convert into Joule heat, resulting in an increase in conductivity loss. This not only significantly reduces the charge and discharge efficiency, but also greatly reduces the breakdown field strength, resulting in failure or damage to power equipment. Therefore, polymer dielectric materials suitable for high temperature environments not only need to have excellent dielectric properties with high dielectric constant and low dielectric loss, but also must have low conductivity loss and high breakdown field strength to ensure high charge and discharge efficiency and high discharge energy density.

[0003] At present, high-temperature polymer dielectric materials used for film capacitors are mainly thermoplastic engineering plastics with high glass transition temperature (Tg), such as polyetherimide (PEI), polyphenylene sulfide (PPS), polyester (PET) and polyetheretherketone (PEEK). Although these materials have a high Tg and can meet the mechanical temperature resistance requirements, their dielectric energy storage performance at high temperatures is still not ideal. For example, at 150°C, the conductivity loss increases significantly, resulting in a significant decrease in breakdown field strength, charge and discharge efficiency, and energy storage density. Therefore, the development of new polymer dielectric materials with excellent dielectric energy storage performance in a wide temperature range (from room temperature to 150°C) has important application prospects. Summary of the invention

[0004] In view of the problem that the existing polymer dielectrics have insufficient dielectric energy storage performance under high temperature and strong electric field, the purpose of the present invention is to provide a full-polymer nanostructured dielectric film with self-assembled nanoscale multi-interfaces and a preparation method thereof.

[0005] In order to achieve the above-mentioned object of the invention, the technical solution adopted by the present invention is:

[0006] On the one hand, a fully polymer nanostructured dielectric film with self-assembled nanoscale multi-interfaces is provided, wherein the composition of the film material meets the following requirements:

[0007] The mass ratio of the thermoplastic resin to the bismaleimide resin is 95:5-65:35; the amount of the catalyst added is 0.05wt%-2wt% of the weight of the bismaleimide resin;

[0008] The thermoplastic polymer is a thermoplastic material with a high glass transition temperature; the catalyst is an initiator for the chain extension reaction and the cross-linking reaction of the bismaleimide resin.

[0009] Furthermore, the mass ratio of the thermoplastic resin to the bismaleimide resin is 85:15-70:30.

[0010] Furthermore, the added amount of the catalyst is 0.1wt%-1wt% of the weight of the bismaleimide resin.

[0011] Furthermore, the thermoplastic polymer is polyetherimide, polysulfone or polycarbonate.

[0012] Furthermore, the bismaleimide resin is bisphenol A bismaleimide or 4,4'-diphenylmethane bismaleimide.

[0013] Furthermore, the catalyst is di-tert-butyl peroxyisopropylbenzene or di-tert-butyl peroxide.

[0014] On the other hand, a method for preparing a fully polymer nanostructured dielectric film having a self-assembled nanoscale multi-interface is provided, comprising the following steps:

[0015] S1. The thermoplastic polymer and the bismaleimide resin are placed in a polar organic solvent and heated to dissolve; a catalyst is added to obtain a slurry of the composition, the solid content of the slurry being 0.1wt%-20wt%;

[0016] S2. After the slurry is evenly coated on the glass substrate, it is baked at 60-90 ° C for more than 10 hours to evaporate the solvent as much as possible to obtain an uncured film;

[0017] S3. After the solvent is evaporated, the glass substrate is subjected to a curing reaction at multiple temperatures between 200°C and 250°C to obtain a cured film;

[0018] S4. Put the glass substrate with the cured film into deionized water to peel off the film, and dry the peeled film at high temperature to obtain a fully polymer nanostructured dielectric film with self-assembled nanoscale multi-interfaces.

[0019] Furthermore, in step S1, the solid content of the slurry is 1wt%-2wt%.

[0020] Furthermore, in step S3, the temperature and time of each stage of the curing reaction are: 200° C. for two hours, and 230° C. for six hours.

[0021] The beneficial effects of the present invention are:

[0022] The present invention provides a fully polymer nanostructured dielectric film with self-assembled nanoscale multi-interfaces, which can meet the application requirements under conditions of 150°C and above 600MV / m. The thermoplastic resin component in the film gives it good flexibility, which is suitable for the winding and lamination processes of film capacitors; and the bismaleimide (BMI) nanoscale multi-interface structure effectively blocks the injection and excitation of charges, significantly reducing the leakage current under high temperature and strong electric field, thereby improving its dielectric energy storage performance under high temperature and strong electric field conditions. When used as a film capacitor, it exhibits excellent device performance in a wide temperature range (room temperature to 150°C), and is suitable for power electronic devices and microelectronic devices such as energy storage capacitors, embedded capacitors, and organic field effect transistors in high temperature environments. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 The energy storage density diagram of the all-polymer nanostructured dielectric film with self-assembled nanoscale multi-interfaces obtained in Examples 1 to 3 of the present invention;

[0024] Figure 2 The graphs showing the changes in dielectric constant and dielectric loss with frequency of the all-polymer nanostructured dielectric films with self-assembled nanoscale multi-interfaces obtained in Examples 1 to 3 of the present invention;

[0025] Figure 3 The graphs showing the changes in dielectric constant and dielectric loss with temperature of the all-polymer nanostructured dielectric films with self-assembled nanoscale multi-interfaces obtained in Examples 1 to 3 of the present invention;

[0026] Figure 4 The energy storage density diagram of the dielectric films obtained in Comparative Examples 1 to 6 of the present invention;

[0027] Figure 5 The graphs are the changes of the dielectric constant and dielectric loss of the dielectric films obtained in Comparative Examples 1 to 6 of the present invention with the frequency;

[0028] Figure 6 The graphs showing the changes of the dielectric constant and dielectric loss of the dielectric films obtained in Comparative Examples 1 to 3 of the present invention with temperature;

[0029] Figure 7 DE curves of the all-polymer nanostructured dielectric film / PEI dielectric film with self-assembled nanoscale multi-interfaces obtained in Example 1 of the present invention and Comparative Example 1;

[0030] Figure 8DE curves of the all-polymer nanostructured dielectric film / PC dielectric film with self-assembled nanoscale multi-interfaces obtained in Example 2 of the present invention and Comparative Example 2;

[0031] Fig. 9 DE curves of the all-polymer nanostructured dielectric film / PSU dielectric film with self-assembled nanoscale multi-interfaces obtained in Example 3 of the present invention and Comparative Example 3;

[0032] Fig.10 This is a SEM image of the all-polymer nanostructured dielectric film with self-assembled nanoscale multi-interfaces obtained in Example 1 of the present invention;

[0033] Fig.11 This is a SEM image of the all-polymer nanostructured dielectric film with self-assembled nanoscale multi-interfaces obtained in Example 2 of the present invention;

[0034] Fig.12 This is a SEM image of the all-polymer nanostructured dielectric film with self-assembled nanoscale multi-interfaces obtained in Example 3 of the present invention;

[0035] Fig.13 This is a SEM image of the dielectric film obtained in Comparative Example 1 of the present invention;

[0036] Fig.14 This is a SEM image of the dielectric film obtained in Comparative Example 2 of the present invention;

[0037] Fig.15 This is a SEM image of the dielectric film obtained in Comparative Example 3 of the present invention;

[0038] Fig.16 This is a SEM image of the dielectric film obtained in Comparative Example 4 of the present invention;

[0039] Fig.17 This is a SEM image of the dielectric film obtained in Comparative Example 5 of the present invention;

[0040] Fig.18 This is a SEM image of the dielectric film obtained in Comparative Example 6 of the present invention;

[0041] Fig.19 This is a SEM image of the dielectric film obtained in Comparative Example 7 of the present invention. DETAILED DESCRIPTION

[0042] The specific implementation modes of the present invention are described below so that those skilled in the art can understand the present invention. However, it should be clear that the present invention is not limited to the scope of the specific implementation modes. For those of ordinary skill in the art, as long as various changes are within the spirit and scope of the present invention as defined and determined by the attached claims, these changes are obvious, and all inventions and creations utilizing the concept of the present invention are protected.

[0043] The all-polymer nanostructured dielectric film with self-assembled nanoscale multi-interfaces of Examples 1 to 3 of the present invention comprises the following components:

[0044] (1) Thermoplastic polymer, which imparts film-forming properties to the uncured film (B-stage Film), toughness to the self-assembled nanoscale multi-interface polymer film after curing, and basic dielectric properties and high-temperature energy storage properties. The thermoplastic polymer is selected from one of thermoplastic polymers with a high glass transition temperature such as polyetherimide (PEI), polysulfone (PSU), and polycarbonate (PC).

[0045] (2) Bismaleimide (BMI) resin. After curing and cross-linking, the BMI resin gives the film (C-stage Film) a self-assembled nanoscale multi-interface structure, thereby giving the film excellent high-temperature energy storage performance. BMI is selected from one of bisphenol A bismaleimide (BPA) or 4,4'-diphenylmethane bismaleimide (BDM).

[0046] (3) Catalyst, an initiator of the chain extension reaction and cross-linking reaction of BMI, which can reduce the reaction temperature and increase the reaction rate. The catalyst is selected from one of the free radical initiators with a half-life of 1 min / °C higher than the melting point of BMI (about 180°C), such as di-tert-butyl peroxyisopropylbenzene (BIPB) and di-tert-butyl peroxide (DTPB).

[0047] (4) The content relationship between the components is: the mass ratio of thermoplastic resin to bismaleimide resin is 95:5-65:35, preferably 90:10-70:30; the added amount of catalyst is 0.05wt%-2wt% of the weight of BMI, preferably 0.1wt%-1wt%.

[0048] Example 1: The raw materials involved in this example include PEI, BPA, and BIPB.

[0049] The preparation steps are as follows:

[0050] 1. Mix polyetherimide (PEI) and bisphenol A bismaleimide (BPA) in a mass ratio of 75:25, add 1wt% (relative to BPABMI) of di-tert-butyl peroxyisopropylbenzene (BIPB) free radical initiator, and prepare a solution with a concentration of 2wt%. For example, weigh 0.15g of polyetherimide (PEI), 0.05g of bisphenol A bismaleimide (BPA), 0.0005g of di-tert-butyl peroxyisopropylbenzene (BIPB), and add 10ml of N-methylpyrrolidone (NMP) to prepare a solution.

[0051] 2. Heat the above solution to 50°C under magnetic stirring and dissolve and disperse for 8 hours to allow the solute to be fully and evenly dissolved in the solvent.

[0052] 3. Clean the glass slide to avoid dust contamination, then put the glass slide in a 70℃ oven for preheating for half an hour, then use a rubber-tipped dropper to absorb 5 ml of the film-making liquid and drop it onto the glass slide, and let the glass slide be baked in a 70℃ oven for 10 hours to evaporate the solvent.

[0053] 4. After the solvent has evaporated, the glass sheet is placed in a vacuum oven and the temperature is adjusted to perform a multi-stage curing reaction. The temperature and time of each stage are: 200°C for two hours, 230°C for six hours, and the cured film is obtained after natural cooling.

[0054] 5. Soak the glass sheet with the cured film in deionized water. After a period of time, the film will fall off the glass sheet by itself. Wrap the fallen film with aluminum foil.

[0055] 6. The aluminum foil wrapped with the film was placed in a vacuum oven and dried at 120° C. for 10 hours to obtain a PEI / BPA (75 / 25) all-polymer nanostructured dielectric film with self-assembled nanoscale multi-interfaces.

[0056] Implementation effect: The energy storage density of the PEI / BPA (75 / 25) dielectric film with self-assembled nanoscale multi-interfaces is as follows: Figure 1 As shown in the figure, it has high energy storage density and efficiency at 150°C. When the electric field strength is 650MV / m, the charge and discharge efficiency is still 91.9%, and the discharge energy density is 6.76J / cm 3 The dielectric constant and dielectric loss of the PEI / BPA (75 / 25) all-polymer nanostructured dielectric film with self-assembled nanoscale multi-interfaces prepared in this example vary with frequency as shown in Figure 2As shown in FIG. 1 , when the frequency is 1 MHz, the dielectric constant is 3.39 and the dielectric loss is 0.01. This composition has a high dielectric constant and a low dielectric loss. The dielectric constant and dielectric loss of the PEI / BPA (75 / 25) dielectric film with self-assembled nanoscale multi-interfaces prepared in this example vary with temperature as shown in FIG. Figure 3 As shown in FIG. 1 , the composition has a stable dielectric constant and dielectric loss from room temperature to 200° C. The DE curve of the PEI / BPA (75 / 25) all-polymer nanostructured dielectric film with self-assembled nanoscale multi-interfaces prepared in this example is shown in FIG. Figure 7 As shown in FIG. 1 , the thinner DE ring indicates that the all-polymer nanostructured dielectric film with self-assembled nanoscale multi-interfaces has high energy storage efficiency. The SEM image of the PEI / BPA (75 / 25) all-polymer nanostructured dielectric film with self-assembled nanoscale multi-interfaces prepared in this example is shown in FIG. Fig.10 As shown, the spherical domains formed by BPA have a smaller particle size and have good compatibility with the PEI matrix.

[0057] Example 2: The raw materials involved in this example include PC, BPA, and BIPB.

[0058] The preparation steps are as follows:

[0059] 1. Mix polycarbonate (PC) and bisphenol A bismaleimide (BPA) in a mass ratio of 75:25, add 1wt% (relative to BPA) of di-tert-butyl peroxy isopropylbenzene (BIPB) free radical initiator, and prepare a solution with a concentration of 2wt%. For example, weigh 0.15g of polycarbonate (PC), 0.05g of bisphenol A bismaleimide (BPA), 0.0005g of di-tert-butyl peroxy isopropylbenzene (BIPB), and add 10ml of N-methylpyrrolidone (NMP) to prepare a solution.

[0060] 2. Heat the above solution to 50°C under magnetic stirring and dissolve and disperse for 8 hours to allow the solute to be fully and evenly dissolved in the solvent.

[0061] 3. Clean the glass slide to avoid dust contamination, then put the glass slide in a 70℃ oven for preheating for half an hour, then use a rubber-tipped dropper to absorb 5 ml of the film-making liquid and drop it onto the glass slide, and let the glass slide be baked in a 70℃ oven for 10 hours to evaporate the solvent.

[0062] 4. After the solvent has evaporated, the glass sheet is placed in a vacuum oven and the temperature is adjusted to perform a multi-stage curing reaction. The temperature and time of each stage are: 200°C for two hours, 230°C for six hours, and the cured film is obtained after natural cooling.

[0063] 5. Soak the glass sheet with the cured film in deionized water. After a period of time, the film will fall off the glass sheet by itself. Wrap the fallen film with aluminum foil.

[0064] 6. The aluminum foil wrapped with the film was placed in a vacuum oven and dried at a high temperature of 120° C. for 10 hours to obtain a PC / BPA (75 / 25) all-polymer nanostructured dielectric film with self-assembled nanoscale multi-interfaces.

[0065] Implementation effect: The energy storage density of the PC / BPA (75 / 25) dielectric film with self-assembled nanoscale multi-interfaces is as follows: Figure 1 As shown in the figure, it has high energy storage density and efficiency at 150°C. When the electric field strength is 600MV / m, the charge and discharge efficiency is still 90.8%, and the discharge energy density is 6.14J / cm 3 The dielectric constant and dielectric loss of the PC / BPA (75 / 25) dielectric film with self-assembled nanoscale multi-interfaces prepared in this example vary with frequency. Figure 2 As shown in FIG. 1 , when the frequency is 1 MHz, the dielectric constant is 2.86 and the dielectric loss is 0.007. This composition has a high dielectric constant and a low dielectric loss. The dielectric constant and dielectric loss of the PEI / BPA (75 / 25) dielectric film with self-assembled nanoscale multi-interfaces prepared in this example vary with temperature as shown in FIG. Figure 3 As shown in FIG. 1 , the composition has a stable dielectric constant and dielectric loss from room temperature to 200° C. The DE curve of the PC / BPA (75 / 25) dielectric film with self-assembled nanoscale multi-interfaces prepared in this example is shown in FIG. Figure 8 As shown in FIG. 1 , the thinner DE ring indicates that the all-polymer nanostructured dielectric film with self-assembled nanoscale multi-interfaces has high energy storage efficiency. The SEM image of the PC / BPA (75 / 25) all-polymer nanostructured dielectric film with self-assembled nanoscale multi-interfaces prepared in this example is shown in FIG. Fig.11 As shown in the figure, the spherical domains formed by BPA have a smaller particle size and have good compatibility with the PC matrix.

[0066] Example 3: The raw materials involved in this example include PSU, BPA, and BIPB.

[0067] The preparation steps are as follows:

[0068] 1. Mix polysulfone (PSU) and bisphenol A bismaleimide (BPA) in a mass ratio of 75:25, add 1wt% (relative to BPA) of di-tert-butyl peroxy isopropylbenzene (BIPB) free radical initiator, and prepare a solution with a concentration of 2wt%. For example, weigh 0.15g of polysulfone (PSU), 0.05g of bisphenol A bismaleimide (BPA), 0.0005g of di-tert-butyl peroxy isopropylbenzene (BIPB), and add 10ml of N-methylpyrrolidone (NMP) to prepare a solution.

[0069] 2. Heat the above solution to 50°C under magnetic stirring and dissolve and disperse for 8 hours to allow the solute to be fully and evenly dissolved in the solvent.

[0070] 3. Clean the glass slide to avoid dust contamination, then put the glass slide in a 70℃ oven for preheating for half an hour, then use a rubber-tipped dropper to absorb 5 ml of the film-making liquid and drop it onto the glass slide, and let the glass slide be baked in a 70℃ oven for 10 hours to evaporate the solvent.

[0071] 4. After the solvent has evaporated, the glass sheet is placed in a vacuum oven and the temperature is adjusted to perform a multi-stage curing reaction. The temperature and time of each stage are: 200°C for two hours, 230°C for six hours, and the cured film is obtained after natural cooling.

[0072] 5. Soak the glass sheet with the cured film in deionized water. After a period of time, the film will fall off the glass sheet by itself. Wrap the fallen film with aluminum foil.

[0073] 6. The aluminum foil wrapped with the film was placed in a vacuum oven and dried at 120° C. for 10 hours to obtain a PSU / BPA (75 / 25) all-polymer nanostructured dielectric film with self-assembled nanoscale multi-interfaces.

[0074] Implementation effect: The energy storage density of the PSU / BPA (75 / 25) dielectric film with self-assembled nanoscale multi-interfaces prepared in this embodiment is as follows: Figure 1 As shown in the figure, it has high energy storage density and efficiency at 150°C. When the electric field strength is 550MV / m, the charge and discharge efficiency is still 90.1%, and the discharge energy density is 4.89J / cm 3 The dielectric constant and dielectric loss of the PSU / BPA (75 / 25) all-polymer nanostructured dielectric film with self-assembled nanoscale multi-interfaces prepared in this example vary with frequency as shown in Figure 2As shown in FIG. 1 , when the frequency is 1 MHz, the dielectric constant is 3.06 and the dielectric loss is 0.009. This composition has a high dielectric constant and a low dielectric loss. The dielectric constant and dielectric loss of the PSU / BPA (75 / 25) dielectric film with self-assembled nanoscale multi-interfaces prepared in this embodiment vary with temperature as shown in FIG. Figure 3 As shown in FIG. 1 , the composition has a stable dielectric constant and dielectric loss from room temperature to 200° C. The DE curve of the PSU / BPA (75 / 25) all-polymer nanostructured dielectric film with self-assembled nanoscale multi-interfaces prepared in this example is shown in FIG. Fig. 9 As shown in FIG. 1 , the thinner DE ring indicates that the all-polymer nanostructured dielectric film with self-assembled nanoscale multi-interfaces has high energy storage efficiency. The SEM image of the PSU / BPA (75 / 25) all-polymer nanostructured dielectric film with self-assembled nanoscale multi-interfaces prepared in this example is shown in FIG. Fig.11 As shown in the figure, the spherical domains formed by BPA have a small particle size and have good compatibility with the PSU matrix.

[0075] Comparative Example 1: The raw materials involved in this comparative example include PEI.

[0076] 1. Weigh 0.2 g of polyetherimide (PEI) and add 10 ml of N-methylpyrrolidone (NMP) to prepare a solution.

[0077] 2. Place the glass bottle containing the membrane-forming solution on a magnetic stirring table heated at 50°C and stir for 8 hours to allow the solute to fully and evenly dissolve in the solvent.

[0078] 3. Clean the glass slide to avoid dust contamination, then put the glass slide in a 70℃ oven for preheating for half an hour, then use a rubber-tipped dropper to absorb 5 ml of the film-making liquid and drop it onto the glass slide, and let the glass slide be baked in a 70℃ oven for 10 hours to evaporate the solvent.

[0079] 4. After the solvent has evaporated, the glass sheet is placed in a vacuum oven and the temperature is adjusted to perform a multi-stage curing reaction. The temperature and time of each stage are: 200°C for two hours, 230°C for six hours, and the cured film is obtained after natural cooling.

[0080] 5. Soak the glass sheet with the cured film in deionized water. After a period of time, the film will fall off the glass sheet by itself. Wrap the fallen film with aluminum foil.

[0081] 6. Place the aluminum foil wrapped with the film in a vacuum oven and dry it at 120°C for 10 hours to obtain a PEI dielectric film.

[0082] Comparative effect: The energy storage density of the PEI dielectric film prepared in this comparative example is as follows Figure 4 As shown in Figure 2, it has low energy storage density and efficiency at 150°C. When the electric field strength is 600MV / m, the charge and discharge efficiency is only 72.4%, and the discharge energy density is 5.28J / cm 3 The dielectric constant and dielectric loss of the dielectric film prepared in this comparative example vary with frequency as shown in Figure 5 As shown in FIG. 1 , when the frequency is 1 MHz, the dielectric constant is 3.29 and the dielectric loss is 0.0066. The dielectric constant and dielectric loss of the dielectric film prepared in this comparative example vary with temperature as shown in FIG. Figure 6 The DE curve of the dielectric film prepared in this comparative example is shown in Figure 7 As shown in FIG. 1 , the thicker DE ring indicates that the dielectric film has a low energy storage efficiency. The SEM image of the PEI dielectric film prepared in this comparative example is shown in FIG. Fig.13 shown.

[0083] Comparative Example 2: The raw materials involved in this comparative example include PC.

[0084] 1. Weigh 0.2 g of polycarbonate (PC) and add 10 ml of N,N-dimethylformamide (DMF) to make a solution.

[0085] 2. Place the glass bottle containing the membrane-forming solution on a magnetic stirring table heated at 50°C and stir for 8 hours to allow the solute to fully and evenly dissolve in the solvent.

[0086] 3. Clean the glass slide to avoid dust contamination, then put the glass slide in a 70℃ oven for preheating for half an hour, then use a rubber-tipped dropper to absorb 5 ml of the film-making liquid and drop it onto the glass slide, and let the glass slide be baked in a 70℃ oven for 10 hours to evaporate the solvent.

[0087] 4. After the solvent has evaporated, the glass sheet is placed in a vacuum oven and baked at 150°C for 10 hours. After natural cooling, a solidified film is obtained.

[0088] 5. Soak the glass sheet with the cured film in deionized water. After a period of time, the film will fall off the glass sheet by itself. Wrap the fallen film with aluminum foil.

[0089] 6. Place the aluminum foil wrapped with the film in a vacuum oven and dry it at 120°C for 10 hours to obtain a PC dielectric film.

[0090] Comparative effect: The energy storage density of the PC dielectric film prepared in this comparative example is as follows Figure 4 As shown in Figure 2, it has low energy storage density and efficiency at 150°C. When the electric field strength is 450MV / m, the charge and discharge efficiency is only 73.5%, and the discharge energy density is 2.32J / cm 3The dielectric constant and dielectric loss of the dielectric film prepared in this comparative example vary with frequency as shown in Figure 5 As shown in FIG. 1 , when the frequency is 1 MHz, the dielectric constant is 3.00 and the dielectric loss is 0.009. The dielectric constant and dielectric loss of the dielectric film prepared in this comparative example vary with temperature as shown in FIG. Figure 6 The DE curve of the dielectric film prepared in this comparative example is shown in Figure 8 As shown in FIG. 1 , the thicker DE ring indicates that the dielectric film has a low energy storage efficiency. The SEM image of the PC dielectric film prepared in this comparative example is shown in FIG. Fig.14 shown.

[0091] Comparative Example 3: The raw materials involved in this comparative example include PSU.

[0092] 1. Weigh 0.2 g of polysulfone (PSU) and add 10 ml of N-methylpyrrolidone (NMP) to make a solution.

[0093] 2. Place the glass bottle containing the membrane-forming solution on a magnetic stirring table heated at 50°C and stir for 8 hours to allow the solute to fully and evenly dissolve in the solvent.

[0094] 3. Clean the glass slide to avoid dust contamination, then put the glass slide in a 70℃ oven for preheating for half an hour, then use a rubber-tipped dropper to absorb 5 ml of the film-making liquid and drop it onto the glass slide, and let the glass slide be baked in a 70℃ oven for 10 hours to evaporate the solvent.

[0095] 4. After the solvent has evaporated, the glass sheet is placed in a vacuum oven and the temperature is adjusted to perform a multi-stage curing reaction. The temperature and time of each stage are: 200°C for two hours, 230°C for six hours, and the cured film is obtained after natural cooling.

[0096] 5. Soak the glass sheet with the cured film in deionized water. After a period of time, the film will fall off the glass sheet by itself. Wrap the fallen film with aluminum foil.

[0097] 6. Place the aluminum foil wrapped with the film in a vacuum oven and dry it at 120°C for 10 hours to obtain a PSU dielectric film.

[0098] Comparative effect: The energy storage density of the PSU dielectric film prepared in this comparative example is as follows Figure 4 As shown in Figure 2, it has low energy storage density and efficiency at 150°C. When the electric field strength is 550MV / m, the charge and discharge efficiency is only 77.5%, and the discharge energy density is 4.99J / cm 3 The dielectric constant and dielectric loss of the dielectric film prepared in this comparative example vary with frequency as shown in Figure 5As shown in FIG. 1 , when the frequency is 1 MHz, the dielectric constant is 3.02 and the dielectric loss is 0.007. The dielectric constant and dielectric loss of the dielectric film prepared in this comparative example vary with temperature as shown in FIG. Figure 6 The DE curve of the dielectric film prepared in this comparative example is shown in Fig. 9 As shown in FIG. 1 , the thicker DE ring indicates that the dielectric film has a low energy storage efficiency. The SEM image of the PSU dielectric film prepared in this comparative example is shown in FIG. Fig.15 shown.

[0099] Comparative Example 4: The raw materials involved in this comparative example include PEI, BPA, and BIPB.

[0100] The preparation steps are as follows:

[0101] 1. Mix polyetherimide (PEI) and bisphenol A bismaleimide (BPA) in a mass ratio of 90:10, add 1wt% (relative to BPA) of di-tert-butyl peroxyisopropylbenzene (BIPB) free radical initiator, and prepare a solution with a concentration of 2wt%. For example, weigh 0.18g of polyetherimide (PEI), 0.02g of bisphenol A bismaleimide (BPA), 0.0002g of di-tert-butyl peroxyisopropylbenzene (BIPB), and add 10ml of N-methylpyrrolidone (NMP) to prepare a solution.

[0102] 2. Heat the above solution to 50°C under magnetic stirring and dissolve and disperse for 8 hours to allow the solute to be fully and evenly dissolved in the solvent.

[0103] 3. Clean the glass slide to avoid dust contamination, then put the glass slide in a 70℃ oven for preheating for half an hour, then use a rubber-tipped dropper to absorb 5 ml of the film-making liquid and drop it onto the glass slide, and let the glass slide be baked in a 70℃ oven for 10 hours to evaporate the solvent.

[0104] 4. After the solvent has evaporated, the glass sheet is placed in a vacuum oven and the temperature is adjusted to perform a multi-stage curing reaction. The temperature and time of each stage are: 200°C for two hours, 230°C for six hours, and the cured film is obtained after natural cooling.

[0105] 5. Soak the glass sheet with the cured film in deionized water. After a period of time, the film will fall off the glass sheet by itself. Wrap the fallen film with aluminum foil.

[0106] 6. The aluminum foil wrapped with the film was placed in a vacuum oven and dried at 120° C. for 10 hours to obtain a PEI / BPA (90 / 10) all-polymer nanostructured dielectric film with self-assembled nanoscale multi-interfaces.

[0107] Implementation effect: The energy storage density of the PEI / BPA (90 / 10) dielectric film with self-assembled nanoscale multi-interfaces is as follows: Figure 4 As shown in Figure 2, at 150°C and an electric field strength of 600 MV / m, the charge and discharge efficiency is 87.7% and the discharge energy density is 5.42 J / cm 3 The dielectric constant and dielectric loss of the PEI / BPA (90 / 10) dielectric film with self-assembled nanoscale multi-interfaces prepared in this comparative example vary with frequency. Figure 5 As shown in FIG. 1 , when the frequency is 1 MHz, the dielectric constant is 3.42 and the dielectric loss is 0.01. The SEM image of the PEI / BPA (90 / 10) dielectric film with self-assembled nanoscale multi-interfaces prepared in this comparative example is shown in FIG. Fig.16 shown.

[0108] Comparative Example 5: The raw materials involved in this comparative example include PC, BPA, and BIPB.

[0109] The preparation steps are as follows:

[0110] 1. Mix polycarbonate (PC) and bisphenol A bismaleimide (BPA) in a mass ratio of 90:10, add 1wt% (relative to BPA) of di-tert-butyl peroxyisopropylbenzene (BIPB) free radical initiator, and prepare a solution with a concentration of 2wt%. For example, weigh 0.18g of polyetherimide (PEI), 0.02g of bisphenol A bismaleimide (BPA), 0.0002g of di-tert-butyl peroxyisopropylbenzene (BIPB), and add 10ml of N-methylpyrrolidone (NMP) to prepare a solution.

[0111] 2. Heat the above solution to 50°C under magnetic stirring and dissolve and disperse for 8 hours to allow the solute to be fully and evenly dissolved in the solvent.

[0112] 3. Clean the glass slide to avoid dust contamination, then put the glass slide in a 70℃ oven for preheating for half an hour, then use a rubber-tipped dropper to absorb 5 ml of the film-making liquid and drop it onto the glass slide, and let the glass slide be baked in a 70℃ oven for 10 hours to evaporate the solvent.

[0113] 4. Put the glass sheet after the solvent evaporates into a vacuum oven and adjust the temperature to carry out a multi-stage curing reaction. The temperature and time of each stage are: 200°C for two hours, 230°C for six hours, and then naturally cool to obtain a cured film.

[0114] 5. Soak the glass sheet with the cured film in deionized water. After a period of time, the film will fall off the glass sheet by itself. Wrap the fallen film with aluminum foil.

[0115] 6. The aluminum foil wrapped with the film was placed in a vacuum oven and dried at 120° C. for 10 hours to obtain a PC / BPA (90 / 10) all-polymer nanostructured dielectric film with self-assembled nanoscale multi-interfaces.

[0116] Implementation effect: The energy storage density of the PC / BPA (90 / 10) dielectric film with self-assembled nanoscale multi-interfaces is as follows: Figure 4 As shown in Figure 2, at 150°C and an electric field strength of 600MV / m, the charge and discharge efficiency is 72.9% and the discharge energy density is 4.70J / cm 3 The dielectric constant and dielectric loss of the PC / BPA (90 / 10) dielectric film with self-assembled nanoscale multi-interfaces prepared in this comparative example vary with frequency. Figure 5 As shown in FIG. 1 , when the frequency is 1 MHz, the dielectric constant is 2.73 and the dielectric loss is 0.007. The SEM image of the PC / BPA (90 / 10) dielectric film with self-assembled nanoscale multi-interfaces prepared in this comparative example is shown in FIG. Fig.17 shown.

[0117] Comparative Example 6: The raw materials involved in this comparative example include PEI, BDM, and BIPB.

[0118] The preparation steps are as follows:

[0119] 1. Mix polyetherimide (PEI) and 4,4'-diphenylmethane bismaleimide (BDM) in a mass ratio of 75:25, add 1wt% (relative to BDM) of di-tert-butyl peroxyisopropylbenzene (BIPB) free radical initiator, and prepare a solution with a concentration of 2wt%. For example, weigh 0.15g of polyetherimide (PEI), 0.05g of 4,4'-diphenylmethane bismaleimide (BDM), 0.0005g of di-tert-butyl peroxyisopropylbenzene (BIPB), and add 10ml of N-methylpyrrolidone (NMP) to prepare a solution.

[0120] 2. Heat the above solution to 50°C under magnetic stirring and dissolve and disperse for 8 hours to allow the solute to be fully and evenly dissolved in the solvent.

[0121] 3. Clean the glass slide to avoid dust contamination, then put the glass slide in a 70℃ oven for preheating for half an hour, then use a rubber-tipped dropper to absorb 5 ml of the film-making liquid and drop it onto the glass slide, and let the glass slide be baked in a 70℃ oven for 10 hours to evaporate the solvent.

[0122] 4. After the solvent has evaporated, the glass sheet is placed in a vacuum oven and the temperature is adjusted to perform a multi-stage curing reaction. The temperature and time of each stage are: 200°C for two hours, 230°C for six hours, and the cured film is obtained after natural cooling.

[0123] 5. Soak the glass sheet with the cured film in deionized water. After a period of time, the film will fall off the glass sheet by itself. Wrap the fallen film with aluminum foil.

[0124] 6. The aluminum foil wrapped with the film was placed in a vacuum oven and dried at 120° C. for 10 hours to obtain a PEI / BDM (75 / 25) all-polymer nanostructured dielectric film with self-assembled nanoscale multi-interfaces.

[0125] Implementation effect: The energy storage density of the PEI / BDM (75 / 25) dielectric film with self-assembled nanoscale multi-interfaces is as follows: Figure 4 As shown in Figure 2, it has high energy storage density and efficiency at 150°C. When the electric field strength is 600MV / m, the charge and discharge efficiency is 83.2% and the discharge energy density is 6.4J / cm 3 The dielectric constant and dielectric loss of the PEI / BDM (75 / 25) dielectric film with self-assembled nanoscale multi-interfaces prepared in this comparative example vary with frequency. Figure 5 As shown in FIG. 1 , when the frequency is 1 MHz, the dielectric constant is 2.98 and the dielectric loss is 0.008. The SEM image of the PEI / BDM (75 / 25) dielectric film with self-assembled nanoscale multi-interfaces prepared in this comparative example is shown in FIG. Fig.18 As shown in the figure, the domain size formed by BDM is larger and its compatibility with the PEI matrix is ​​poor.

[0126] Comparative Example 7: The raw materials involved in this comparative example include PEI, BPA, and BIPB.

[0127] The preparation steps are as follows:

[0128] 1. Mix polyetherimide (PEI) and bisphenol A bismaleimide (BPA) in a mass ratio of 75:25, add 1wt% (relative to BPABMI) of di-tert-butyl peroxyisopropylbenzene (BIPB) free radical initiator, and prepare a solution with a concentration of 2wt%. For example, weigh 0.15g of polyetherimide (PEI), 0.05g of bisphenol A bismaleimide (BPA), 0.0005g of di-tert-butyl peroxyisopropylbenzene (BIPB), and add 10ml of N-methylpyrrolidone (NMP) to prepare a solution.

[0129] 2. Heat the above solution to 50°C under magnetic stirring and dissolve and disperse for 8 hours to allow the solute to be fully and evenly dissolved in the solvent.

[0130] 3. Clean the glass slide to avoid dust contamination, then put the glass slide in a 70℃ oven for preheating for half an hour, then use a rubber-tipped dropper to absorb 5 ml of the film-making liquid and drop it onto the glass slide, and let the glass slide be baked in a 70℃ oven for 10 hours to evaporate the solvent.

[0131] 4. Place the glass sheet after the solvent has evaporated into a vacuum oven and adjust the temperature to carry out a multi-stage curing reaction. The temperature and time of each stage are: 160°C for two hours, 200°C for two hours, and 230°C for six hours. After natural cooling, a cured film is obtained.

[0132] 5. Soak the glass sheet with the cured film in deionized water. After a period of time, the film will fall off the glass sheet by itself. Wrap the fallen film with aluminum foil.

[0133] 6. Place the aluminum foil wrapped with the film in a vacuum oven and dry it at 120° C. for 10 hours to obtain a PEI / BPA (75 / 25) dielectric film.

[0134] Implementation effect: The microstructure of PEI / BPA (75 / 25) prepared in this comparative example is as follows Fig.19 As shown in the figure, it can be observed that the film prepared by this composition and process forms a homogeneous structure rather than a nanostructure. The reason for this phenomenon is that the process flow first cures at 160°C for 2 hours, and the curing temperature is lower than the glass transition temperature of the thermoplastic polymer matrix PEI and the melting point of BPA. Therefore, during the curing and cross-linking of BPA molecules, the aggregation of BMI molecular chains is restricted, thereby inhibiting the occurrence of phase separation.

[0135] In summary, the all-polymer nanostructured dielectric film with self-assembled nanoscale multi-interfaces prepared by the present invention can withstand a high temperature of 250°C; in particular, it has excellent high-temperature dielectric energy storage performance, and exhibits excellent energy storage performance at a high temperature of 150°C and above 600MV / m and a strong electric field, such as high breakdown field strength (Eb≥600MV / m), high charge and discharge efficiency (η≥90%) and high discharge energy density (Ue≥5J / cm 3 ). Moreover, the preparation method is simple, the raw material cost is low, and it is easy to achieve mass production, which has important industrial prospects.

[0136] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

[0137] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A fully polymer nanostructured dielectric film with self-assembled nanoscale multi-interfaces, characterized in that: The composition of the film material meets the following requirements: The mass ratio of the thermoplastic resin to the bismaleimide resin is 95:5-65:35; the amount of the catalyst added is 0.05wt%-2wt% of the weight of the bismaleimide resin; The thermoplastic polymer is a thermoplastic material with a high glass transition temperature; the catalyst is an initiator for the chain extension reaction and the cross-linking reaction of the bismaleimide resin.

2. The all-polymer nanostructured dielectric film with self-assembled nanoscale multi-interfaces according to claim 1, characterized in that: The mass ratio of the thermoplastic resin to the bismaleimide resin is 85:15-70:

30.

3. The all-polymer nanostructured dielectric film with self-assembled nanoscale multi-interfaces according to claim 1, characterized in that: The added amount of the catalyst is 0.1wt%-1wt% of the weight of the bismaleimide resin.

4. The all-polymer nanostructured dielectric film with self-assembled nanoscale multi-interfaces according to claim 1, characterized in that: The thermoplastic polymer is polyetherimide, polysulfone or polycarbonate.

5. The all-polymer nanostructured dielectric film with self-assembled nanoscale multi-interfaces according to claim 1, characterized in that: The bismaleimide resin is bisphenol A bismaleimide or 4,4'-diphenylmethane bismaleimide.

6. The all-polymer nanostructured dielectric film with self-assembled nanoscale multi-interfaces according to claim 1, characterized in that: The catalyst is di-tert-butyl peroxyisopropylbenzene or di-tert-butyl peroxide.

7. A method for preparing a fully polymer nanostructured dielectric film having self-assembled nanoscale multi-interfaces according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1. The thermoplastic polymer and the bismaleimide resin are placed in a polar organic solvent and heated to dissolve; a catalyst is added to obtain a slurry of the composition, the solid content of the slurry being 0.1wt%-20wt%; S2. The slurry is evenly coated on the glass substrate and then baked to evaporate the solvent as much as possible to obtain an uncured film; S3. After the solvent is evaporated, the glass substrate is subjected to a curing reaction at multiple temperatures between 200°C and 250°C to obtain a cured film; S4. Put the glass substrate with the cured film into deionized water to peel off the film, and dry the peeled film at high temperature to obtain a fully polymer nanostructured dielectric film with self-assembled nanoscale multi-interfaces.

8. The method for preparing the all-polymer nanostructured dielectric film with self-assembled nanoscale multi-interfaces according to claim 7, characterized in that: In step S1, the solid content of the slurry is 1wt%-2wt%.

9. The method for preparing the all-polymer nanostructured dielectric film with self-assembled nanoscale multi-interfaces according to claim 7, characterized in that: In step S2, baking is performed at 60-90° C. for more than 10 hours.

10. The method for preparing the all-polymer nanostructured dielectric film with self-assembled nanoscale multi-interfaces according to claim 7, characterized in that: In step S3, the temperature and time of each stage of the curing reaction are: 200° C. for two hours and 230° C. for six hours.

Citation Information

Patent Citations

  • Bismaleimide-based thermosetting dielectric film, preparation method thereof and capacitor

    CN117186458A

  • Semi-interpenetrating network polymer, composite material, dielectric film and preparation method thereof

    CN117700991A

  • Polyetherimide modified bimalieimide resin

    CN1263901A